At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
The laws of exponents are:
a) (x^n)*(x^m) = x^(n + m)
b) (x^n)/(x^m) = x^(n - m)
c) (x^n)^m = x^(n*m)
Now, let's see the given equations:
1) (x-²)-³ = x⁶ (true)
Here we se the third law, the "c"
(x^(-2))^(-3) = x^(-2*-3) = x^6
Then this equation is correct.
2) (a^m)^n = a^m^n (false)
This law does not exist, this is false.
An example of why this is false is:
Let's use the values:
a = 2, m = 1, and n = 2
then, in the left side we have:
(2^1)^2 = (2)^2 = 4
And in the right side we have:
2^(1^2) = 2^(1) = 2
We can see that we have different things in the left side than in the right side, then that relation is false.
3) a⁰ = 0 (false)
Let's rewrite this as:
a^0 = a^(n - n)
Now we can use the second law to rewrite this as:
a^(n - n) = (a^n)/(a^n)
And we have a number divided by the exact same number, we know that this is equal to 1, then:
(a^n)/(a^n) = 1
this means that:
a^0 = 1.
Then this is also false.
The only correct option is the first one.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.